On the relationship of Judah and Samaria in post-exilic times A farewell to the conflict paradigm - Hensel, Benedikt 1979- (2019)
The relationship of Judah and Samaria in the period from the 6th to the 2nd century B.C.E is currently still being described as an uninterrupted period of ongoing conflicts between Samarian and Judean YHWH-worshippers. This article examines evidence which offers an entirely different picture of Samarian-Judean relations in the post-exilic period: in the Levant in post-exilic times, there were two homologous Yahwisms in Judah and Samaria which existed side by side. It is for this reason that, when studying this formative period, scholars should give due consideration not only to Judah, but also to the North as well.
Keywords: Josephus; Judaisms; Monotheism; Mount Gerizim; Persian Period; Samaritanism; Samaritans; Yahwisms; Yehud